2017
DOI: 10.1111/pace.13169
|View full text |Cite
|
Sign up to set email alerts
|

Eplerenone might affect atrial fibrosis in patients with hypertension

Abstract: Eplerenone reduced the increase of Ad and P-disp with a decrease of PINP and PIIIP, which might translate into reduction of atrial fibrosis. This study showed that eplerenone may be useful as upstream therapy for AF in patients with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(42 reference statements)
0
4
0
2
Order By: Relevance
“…The RAAS is progressively considered a critical player in cardiac fibrosis development. 53 Angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs) [54][55][56][57][58][59] and mineralocorticoid receptor antagonists [60][61][62][63] can reduce atrial fibrosis progression and AF susceptibility, as demonstrated by multiple experimental studies (Table 1). 64 Retrospective trials and meta-analyses of randomized studies demonstrated that administration of ACEIs or ARBs with ACEIs/ARBs of these diseases may have been confounded by indications.…”
Section: Renin-angiotensin-aldosterone System (Raas) Antagonistsmentioning
confidence: 99%
“…The RAAS is progressively considered a critical player in cardiac fibrosis development. 53 Angiotensin-converting enzyme inhibitors (ACEIs), angiotensin receptor blockers (ARBs) [54][55][56][57][58][59] and mineralocorticoid receptor antagonists [60][61][62][63] can reduce atrial fibrosis progression and AF susceptibility, as demonstrated by multiple experimental studies (Table 1). 64 Retrospective trials and meta-analyses of randomized studies demonstrated that administration of ACEIs or ARBs with ACEIs/ARBs of these diseases may have been confounded by indications.…”
Section: Renin-angiotensin-aldosterone System (Raas) Antagonistsmentioning
confidence: 99%
“… 8 Drugs that prevent myocardial fibrosis and improve heart function might be useful for AF. In recent years, accumulating experimental evidence has suggested that the inhibition of atrial fibrosis using drugs, such as eplerenone, 9 aliskiren, 10 and taurine, 11 effectively inhibits AF susceptibility in patients and animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Upstream therapy of atrial fibrillation has become a research hotspot in recent years, such as angiotensin-converting enzyme inhibitor (ACEI), angiotensin II receptor antagonist (ARB), spironolactone, and statins; spironolactone as one of the upstream treatment drugs has become the focus in the field of electrophysiology. Also, the aldosterone receptor antagonists can alleviate myocardial fibrosis, inhibit the excessive secretion of aldosterone, and reduce the phenomenon of "aldosterone escape" [6][7][8]. ACEI and ARB are popular among scholars for their appropriate therapeutic dose since they do not play an obvious role [9].…”
Section: Discussionmentioning
confidence: 99%